Cost‐Efficient Graphitic Carbon Nitride as an Effective Photocatalyst for Antibiotic Degradation: An Insight into the Effects of Different Precursors and Coexisting Ions, and Photocatalytic Mechanism. Issue 1 (4th December 2018) - Tian, Cheng; Zhao, Hui; Mei, Jian; Yang, Shijian
Abstract: In this study, the photocatalytic activity of graphitic carbon nitride (g‐C3 N4 ) synthesized via different precursors (urea, thiourea, and dicyandiamide) is investigated in the degradation process of tetracycline. Owing to the efficient charge separation and transfer, prolonged radiative lifetime of charge, large surface area, and nanosheet morphology, the urea‐derived g‐C3 N4 exhibits superior photocatalytic activity for tetracycline degradation under visible‐light irradiation. This performance can compare with that of most reported g‐C3 N4 ‐based composite photocatalysts. Through the time‐circle degradation experiment, the urea‐derived g‐C3 N4 is found to have an excellent photocatalytic stability. The presence of NO3 −, CH3 COO −, Cl − and SO4 2− ions with the concentration of 10 mm inhibits the photocatalytic activity of urea‐derived g‐C3 N4, where this inhibitory effect is more obvious for Cl − and SO4 2− ions. For the coexisting Cu 2+, Ca 2+, and Zn 2+ ions, the Cu 2+ ion exhibits a significantly higher inhibitory effect than Ca 2+ and Zn 2+ ions for tetracycline degradation. However, both the inhibitory and facilitating effects are observed in the presence of Fe 3+ ion with different concentration. The h +, . OH and . O2 − radicals are confirmed as major oxidation species and a possible photocatalytic mechanism is proposed in a urea‐derived g‐C3 N4 reaction system. This study is of important significance to promote the large‐scale application of g‐C3 N4 photocatalysts in antibiotic wastewater purification. Abstract : A urea‐derived g‐C3 N4 exhibits superior photocatalytic activity for tetrecycline degradation when compared with thiourea and dicyandiamide precursors. The effects of several common coexisting ions and photocatalytic mechanism are revealed.